The impact of artificial intelligence-driven ESG performance on sustainable development of central state-owned enterprises listed companies - Yuping Xiao; Li Xiao (Scientific Reports)
Abstract In recent years, artificial intelligence (AI) technology has rapidly advanced and found widespread application in corporate management. Leveraging AI to enhance Environmental, Social, and Governance (ESG) performance and promote sustainable development has become a focal point for both academia and industry. This study aims to explore the impact of AI-driven ESG practices on the sustainable development performance of central state-owned enterprises in China. It analyzes the specific effects of AI technology in corporate governance, environmental protection, and social responsibility, and evaluates its contribution to the overall sustainable development of enterprises. The study employs a survey method, targeting 200 managers and employees from Central state-owned enterprises. The questionnaire comprises 15 questions covering three dimensions: corporate governance, environmental protection, and social responsibility. Descriptive statistics and correlation analysis are used to conduct an in-depth analysis of the collected data. The results indicate that respondents positively assess central state-owned enterprises in terms of corporate governance, environmental protection, and social responsibility, with particularly strong performance in social responsibility. Additionally, a regression analysis model is constructed. The results demonstrate that AI technology can enhance the practices and foster the sustainable development of central state-owned enterprises. Furthermore, ESG serves as a mediating factor between AI adoption and improvements in sustainable development performance. The findings provide practical insights for improving corporate management efficiency, enhancing environmental performance transparency, and boosting social image and brand value.